DAMPAK KEGIATAN PENYULUHAN TERHADAP PERUBAHAN PERILAKU PETANI SAYURAN DI KOTA PEKANBARU - Roza Yulida; Kausar '; Lena Marjelita (Indonesian Journal of Agricultural Economics, 2012)
The extension aims to change the farmers or peasent behavior; koqnitive, affective, andpsychomotorict. Therefore, the impact of extensional activities can be done byinvestigating the changing of peasents behavior. The purpose of this research is to learndirectly about impact of Extension in changing of Peasents’ behavior in SidomulyoBarat Village, and analyze the significant variables which partially explain the role ofextensionists. The method analysis was regression while it used 30 peasents asrespondents. The results showed, firstly, the roles of extensionist as educator,dissemination information/ innovation, facilitators, and consultant are high. It means theextensionists’ have been doing their task seriously. Secondly, the significant variablesof extensionists’ role that affect to peasent’s behavior are dissemination andsupervision.Keywords: Analysis of Impact, Extension, Change of behavior, Peasants.